P587 Utility of intestinal ultrasound in Inflammatory Bowel Disease patients on management decisions. (27th May 2021) - Abraham, B; Saleh, A; Perry, C
Abstract: Background: Intestinal Ultrasound (IUS) has been gaining momentum in the management of patients with inflammatory bowel disease (IBD). Underutilized in the United States(U.S.), we present the impact of IUS in management decisions in a cohort of IBD patients seen at a tertiary center. Methods: This retrospective study analyzed all IBD patients seen at our institution undergoing IUS as part of routine clinical evaluation. Patient demographics, disease type, clinical activity, laboratory markers, and therapy was obtained. Patients with evidence of inflammation based on IUS characteristics of bowel wall thickening, with additional parameters of mural stratification, mesenteric fat, doppler flow, lymph nodes, dilated bowel, free fluid used as adjunct measures were compared to those without IUS features of activity. Subsequent management plan based on findings were evaluated. Results: Of 148 patients seen for IUS (median age 41 (range 18–81), 67% female), 108(73%) had Crohn's disease (CD), 39(26.4%) had ulcerative colitis (UC), 1(0.7%) had IBD-undetermined (IBD-U) with 111(75%) Caucasians, 9.5% Blacks, 8.8% Asians, and 6.8% Hispanics. Median disease duration was 8 years, range (0–43) with 113(94.1%) on biologic/small molecule therapy and 7(5.8%) on mesalamines. No differences in BMI were noted in those with active disease vs. those in remission. However, we noted 29(19.3%) had fatty liver on ultrasound, which correlated highly with high BMI (31 vs. 24) in those with normal liver (p<0.05). On IUS, 110(66%) of our patients had evidence of disease activity and 56(34%) were in remission. Inflammatory markers ESR and CRP did not correlate to IUS activity. In our UC patients Mayo score correlated to IUS findings but not Harvey Bradshaw Index (HBI) for CD. For those with positive findings on IUS, 29.5% escalated therapy for their IBD, and 13.3% required change in drug mechanism. For those in remission, the majority of patients 43(84.3%) continued their therapy while 3(5.9%) successfully de-escalated therapy. Conclusion: In our study, IUS was useful in providing management decisions in those with active disease especially as there was a lack of correlation to inflammatory markers and HBI scores.